Controlling of Mobile Robot by Using of Predictive Controller - Alireza Rezaee (IAES International Journal of Robotics and Automation (IJRA), 2017)
In this paper implementation of Model PredictiveController on mobile robot was explained. The conductedexperiments show effectiveness of the proposed method oncontrol of the mobile robot. Furthermore the effects of the modelparameters such as control horizon, prediction horizon,weighting factor and signal filter band on the controllerperformance were studied. Finally, a comparison between thedesigned MPC controller and PID and adaptive controllers waspresented demonstrating superior performance of the ModelPredictive Controllers.